RESPONS FUNGSIONAL PARASITOID TRICHOGRAMMA PRETIOSUM TERHADAP TELUR Corcyra cephalonica: PENGARUH KEPADATAN INANG DAN SUHU - Sapdi Sapdi (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2008)
Functional Response of Parasitoid Trichogramma pretiosum on egg-host Corcyra cephalonica: The Effects of Egg-host Density and Temperature Sapdi Jurusan HPT Fakultas Pertanian Universitas Syiah Kuala Banda Aceh ABSTRACT A laboratory study has been conducted to investigate the functional response of parasitoid Trichogramma pretiosum on egg-host, Corcyra cephalonica. The treatments were egg-host density (5, 10, 15, 30, and 60 eggs per pias) and temperature (18 oC, 25oC, and room temperature). The eggs of host were exposed to the parasitoid for 24 hours at the temperature tested. Then, the parasited eggs were reared at room temperature until they were darkened. The number of parasitized eggs was observed. The result of the study showed that the type of functional response of T. pretiosum on eggs of C. Cephalonica was type II. The percentage of parasitization increased with the increase of egg-host density and temperature tested.